Pemetaan dan Klasterisasi Sekolah Muhammadiyah di Kabupaten PPU Berdasarkan Fasilitas, Pendidik dan Tenaga Pendidik Menggunakan Metode K-Means Clustering - M. Riadhus Sholihin; Rudiman (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Yudharta Pasuruan, 2022)
Educational facilities are a part of achieving learning in schools. Facilities that are generally located in schools are classrooms, libraries and toilets which are intended for teachers/educators and students. With the facilities, teachers, and teaching staff are very important to support teaching and learning activities. To make it easier for the government and Muhammadiyah schools to cluster certain schools into several clusters, making it easier to assist and procure school needs within the North Penajam Paser Regency government. Clustering is done by using the K-Means algorithm. The application of the K-Means Algorithm by determining the Cluster value is 3. The results show that each Cluster has its own number of members. Cluster 0 consists of 5 schools, Cluster 1 consists of 8 schools, and Cluster 2 consists of 1 school. Then the results of the increase sequentially obtained Cluster 0, Cluster 2, and finally Cluster 1. Furthermore, in testing the performance of the K-Means algorithm by dividing 3 clusters, the Davies Bouldin Index value of 0.446 was obtained. From the results of data analysis and processing, there are 8 schools in the low cluster, so this study recommends the need for assistance and provision of school needs for the low cluster by the education office of the North Penajam Paser Regency.